Mitochondrial DNA methylation drift and postoperative delirium in mice. Issue 2 (February 2022) - Liu, Yue; Song, Fen; Yang, Yan; Yang, Shuai; Jiang, Ming; Zhang, Wei; Ma, Zhengliang; Gu, Xiaoping
Abstract : BACKGROUND: Mitochondrial dysfunction is linked to the etiopathogenesis of postoperative delirium (POD), which severely affects the prognosis of elderly patients undergoing surgery. The methylation of mitochondrial DNA (mtDNA), a new and incompletely described phenomenon that regulates the structure and function of mitochondria, is associated with ageing. However, the relationship between mtDNA methylation and POD has not been established. OBJECTIVE: To explore the potential roles of mitochondrial epigenetic regulation in POD. DESIGN: A randomised animal study. PARTICIPANTS: Eighty-eight 6-month-old and one hundred seventy-six 18-month-old male C57BL/6N mice. INTERVENTIONS: POD was induced by abdominal surgery under 1.4% isoflurane for 2 h. Behavioural tests were performed at 24 h before surgery and at 6, 9 and 24 h after surgery. MAIN OUTCOME MEASURES: 5-methylcytosine (5-mC) at five CpG sites of the displacement loop (D-loop) and at 60 CpG sites of coding gene loci in the mitochondrial genome after surgery of the hippocampus, prefrontal cortex, amygdala and anterior cingulate cortex in 6 and 18-month-old mice were detected using bisulfite pyrosequencing. Mitochondrial structure, mitochondrial gene expression and mtDNA copy number were also examined using Electron microscopy and real time PCR to find the association with mtDNA methylation. RESULTS: The mtDNA methylation drift manifested as a decrease in the methylation levels at the D-loop and an increase or decrease in the methylation levels at several coding gene loci, ultimately resulting in reduced mtDNA copy numbers, altered mitochondrial gene expression and damaged mitochondrial structures in the hippocampus and prefrontal cortex after surgery. The activation of Silent information regulator-1 (SIRT1) ameliorated anaesthesia-induced and surgery-induced mitochondrial dysfunction and delirium-like behaviours by regulating mtDNA methyltransferase-mediated mtDNA methylation. CONCLUSION: These data support the existence of epigenetic mtDNA regulation in POD; however, further studies are required to explore the specific mechanisms. TRIAL REGISTRATION: No 20181204 Drum tower hospital. Abstract : Supplemental Digital Content is available in the text